Developing Bowling Letters Media Through NHT Learning Model in Interpreting New Indonesian Vocabulary: A Lesson from Primary Schools Learners - Nurfahada, Afina; SB, Nugraheti Sismulyasih (Universitas Pendidikan Mandalika, 2025)
This research introduces a learning media for javelin letters using wooden boards developed with the Number Head Together (NHT) model to interpret new vocabulary for grade 1 elementary school students. This problem occurs due to low concentration and mastery of understanding in grade 1 elementary school students, thus encouraging researchers to develop effective learning media. This study aims to develop, validate, and test the effectiveness of javelin letters media in interpreting new vocabulary. This study uses a development approach that combines product design stages, feasibility validation by expert validators, and effectiveness testing through small-scale and large-scale trials involving 17 male students and 8 female students in grade 1 of AL HIKMAH Elementary School, Semarang City. The feasibility assessment conducted by experts showed a high level of suitability for the use of the media, with a significant increase in student learning outcomes during the trial. The small-scale trial showed an increase in the average pretest score to the posttest from 52.5 to 77.5 with a significant difference of 25. The large-scale trial showed an increase in the average from 60.2 to 81 with a difference of 20.8. The results of the N-Gain test showed a moderate effect, with a value of 0.5356 for small-scale testing and 0.5437 for large-scale testing. This study concludes that the letter throwing media through the Number Head Together (NHT) model is a very important learning medium for improving understanding of new vocabulary. Positive feedback from teachers and students confirms its effectiveness in generating student engagement to improve learning outcomes in the classroom to be more optimal.